Mass spectrometry in the characterization of reactive metal alkoxides. Issue 1 (4th April 2016) - Peruzzo, Valentina; Chiurato, Matteo Andrea; Favaro, Monica; Tomasin, Patrizia
Abstract : Metal alkoxides are metal‐organic compounds characterized by the presence of MOC bonds (M = metal). Their chemistry seems to be, in principle, relatively simple but the number of possible reactant species arising as a consequence of their behavior is very remarkable. The physico‐chemical properties of metal alkoxides are determined by many different parameters, the most important ones being the electronegativity of the metal, the ramification of the ligand, and the acidity of the corresponding alcohol. Their reactivity makes them suitable and versatile candidates for many applications, including homogeneous catalysis, synthesis of new ceramic materials through the sol‐gel process and, recently, also for Cultural Heritage. Metal alkoxides are characterized by a strong tendency to give clusters and/or oligomers through oxo‐bridges. Mass spectrometry has been successfully employed for the characterization of metal alkoxides in the gas‐phase. Electron ionization (EI) allowed the assessment of the molecular weight and of the most relevant decomposition pathways giving information on the relative bond strength of differently substituted molecules. On the other hand, information on the reactivity in solution of these molecules have been obtained by electrospray ionization (ESI)‐matrix assisted laser desorption ionization (MALDI) experiments performed on their reaction products. These data were relevant to investigate the sol‐gel process. In this review, these aspects are described and the results obtained are critically evaluated. © 2016 Wiley Periodicals, Inc. Mass Spec Rev